Students’ Attitudes in Experiencing Bilingual Environment in Islamic Boarding Schools - Putri Lasminiar (Research And Innovation In Language Learning (RILL), 2022)
This study aimed to describe students’ attitudes in experiencing a bilingual (English-Arabic) environment placed in their Islamic boarding school. This research employed a survey design. The data was obtained from a five-point scale questionnaire, which consisted of 15 statements, administered to 88 junior high school students of the 2021-2022 academic year. Then, the data was descriptive statistically analyzed The finding showed that students had positive attitudes towards the English-Arabic environment. The students believed that the bilingual environment could assist them to acquire the two languages easily by being used to having the languages with their friends and teachers around their daily lives. Furthermore, the research finding also reveals that the bilingual environment increased students’ vocabulary items, made students have better bilingual communication among their friends, and provided circumstances of language learning that influenced bilingual learners Tujuan dari penelitian ini adalah untuk mendeskripsikan perilaku siswa terhadap lingkungan berbahasa Inggris dan Arab yang terdapat di pondok pesantren mereka. Data dari penelitian ini diperoleh dari kuesioner yang berisi 15 peryataan dengan 5 skala Likert yang diberikan kepada 88 siswa SMP tahun ajaran 2021-2022. Data dianalisa Dengan statistic deskriptif. Hasil penelitian menunjukkan bahwa para siswa menunjukkan perilaku positif tentang keberadaan lingkungan berbahasa Inggris dan Arab di pondok pesantren. Mereka meyakini bahwa lingkungan tersebut dapat membantu mereka dalam mnguasai kedua bahasa tersebut dengan membiasakan diri untuk menggunakan kedua bahasa tersebut dalam berkomunikasi dengan teman dan guru di dalam kehidupan mereka sehari-hari. Selain itu, hasil penelitian juga mengungkapkan bahwa lingkungan dwibahasa tersebut dapat meningkatkan jumlah kosa kata baru, meningkatkan kemampuan komunikasi dwibahasa antar teman, dan menciptakan suasana pembelajaran bahasa bagi siswa dwibahasa